Do Tornadoes relly twist? : Questions and answers about tornadoes and Hurricanes - Berger, Melvin (New York : Scholastic, 2000)
Provides answers to a variety of questions about tornadoes and Hurricanes, including " Where do most tornadoes strike," and " How long do hurricanes last?"
Includes index
Keywords: Tornadoes -- Miscellanea -- Juvenile literature